Mutu Layanan Peserta BPJS Kesehatan: Pendekatan Interaction Quality Dimension - Ruslang; Yanuar Azis, Anugerah; Khaeriah B; Azizah, A. Nur; Mustafa, Idarwati; Mikhrunnisai, Andi; Yakob, Asmirati; Alfiyani, Lina (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2024)
BPJS Kesehatan continues to improve the quality of health services through various facilities that work with it. According to BPJS Kesehatan data in 2021, there are 10,228 puskesmas and 7,078 private clinics as First Level Health Facilities (FKTP), and 2,745 hospitals as Advanced Referral Health Facilities (FKRTL). This study aims to analyze the quality of BPJS Health services from the perspective of participants using the Interaction Quality Dimension approach at Puskesmas Tanasitolo, Wajo Regency, South Sulawesi. The research approach used is quantitative with a descriptive design. Data collection was carried out through distributing questionnaires to 99 respondents, namely BPJS Health participants who met certain criteria. The results showed that the attitude, behavior, and expertise of health workers have a significant impact on BPJS Health patient satisfaction. Therefore, it is important to continue to improve these aspects to ensure optimal health services for BPJS Kesehatan patients at the Puskesmas.